Entrevistas en auto-confrontación: un método en clínica de la actividad - Gabriel Fernández; Yves Clot (Universidade do Porto, 2007)
We present a co-analysis of work methodology and a correlative method that we call a crossed self-confrontation. It involves distinguishing between work done and "real" work. Our aim is to identify the activity´s potential developments, in order to eventually transform their course. The method is composed of three phases. The first involves co-design of the work environment. It is followed by a second phase of video recordings of what the operators do and what they say about it in simple and crossed self-confrontation. The third phase involves the collective´s appropriation of the professional dialogues produced in the self-confrontation. The results obtained with this type of analysis, inseparable from an activity clinic, allows us to approach health as the subject´s power to act on his or her self and environment.